Limited potential for terrestrial carbon sequestration to offset fossil‐fuel emissions in the upper midwestern US. Issue 8 (15th December 2009) - Fissore, Cinzia; Espeleta, Javier; Nater, Edward A; Hobbie, Sarah E; Reich, Peter B
Abstract : Many carbon dioxide (CO2 ) emission‐reduction strategies currently under consideration rely on terrestrial carbon (C) sequestration to offset substantial proportions of CO2 emissions. We estimated C sequestration rates and potential land areas for a diverse array of land‐cover changes in the Upper Midwest of the US, a "best case" region for this study because of its relatively modest CO2 emissions and the large areas of cropland potentially available for conversion. We then developed scenarios that apply some of the most widespread mitigation strategies to the region: the first, which aimed to offset 29% of regional CO2 emissions, required the unrealistic loss of two‐thirds of working cropland; the second, which estimated the emission offset attainable by conversion of 10% of harvested croplands (5.8% of the US total), resulted in <5% CO2 emissions reduction for the region (<1.1% of total US emissions). There is limited capacity for terrestrial C sequestration, so strategies should aim to directly reduce CO2 emissions to mitigate rising atmospheric CO2 concentrations.